Factors Behind Contemporary Rape Myths in Europe: A Systematic Review. - Hyży, Pamela; Mitka, Marlena (Trauma, Violence & Abuse, 2024)
Rape myths are social constructs, deeply rooted in European society. They play a role in maintaining false beliefs about sexual violence and are one of the main factors in sexual abuse behavior. In this review article, the authors focused on the factors influencing the perpetuation and spread of false beliefs regarding sexual violence, its victims, and perpetrators. The goal of the study is to achieve a more profound comprehension of the cultural and social dimensions linked to this occurrence. In conducting the systematic literature review, three databases have been used to search for pertinent articles: ProQuest, Scopus, and ERIH Plus. Only peer-reviewed scientific articles in English published between 2013 and 2023 were deemed eligible. Furthermore, inclusion criteria stipulated that articles must present empirical research of European origin, focusing on the keywords: "myths about rape," "myths about sexual violence," and "myths about rape." In total 2,507 articles were initially identified, with 79 ultimately meeting the inclusion criteria. The analysis revealed the presence of several factors influencing the function of rape myths. These were categorized into sociodemographic, individual, and systemic. The general populace of European society commonly holds beliefs in rape myths. Moreover, numerous studies point to large legal and systemic inequalities that lead to social inequalities and, consequently, to the perpetuation of rape culture through victimization and victim blaming. This review demonstrates the need for future research on sex education as a factor in preventing rape myths.